The Impact of Air Pollution in Industrial Area in Durgapur Region West Bengal, India - Sabirul Sk (Mathematical Statistician and Engineering Applications, 2022)
Air is the most critical natural resource for all human activities. It is required for practically all developmental activities, including power production, agriculture, cooking, and all manufacturing processes. Indeed, the quantity of air required for respiration is far less than that required for other activities. Numerous components of air, most notably nitrogen (N2), carbon dioxide (CO2), oxygen (O2), and water vapour, are the primary elements of air related with biological processes. In India, like in many other industrialized and developing nations, the primary sources of air pollution are factories, thermal power plants, and vehicular emissions. Let us have a look at these sources.